Critical Thinking Skills to Literary Works: A Method of Teaching Language through Literature: Keterampilan Berpikir Kritis Terhadap Karya Sastra: Metode Pengajaran Bahasa melalui Sastra - Abida, Fithriyah Inda Nur (JEES (Journal of English Educators Society), 2016)
Teaching a language has become a challenging task for the teachers to train and to teach language for their students. In present time, the ability to master a language is vital for a language is a powerful means of communicating. Most of us will not focus on the language present in the literature part because our mind sets only towards the grammar. This has made both the teacher and students to ignore the literature part and made them to focus only on grammatical part to learn language. The urge behind using literary works in the teaching a language is to argue that the current attempts to implant literary works to the teaching of a language definitely develop students’ critical thinking in such a way that help them to easily master a particular language. Learning literary works in a classroom not only make the students learn about a story but also study how the language are structured and how its structured bring a great difference in meaning. Through a literary works student sees the language of real-life contexts. They learn the feelings, ideas, and experiences of linguistics components that give a realistic touch and help them to learn a language in a comprehensive way. It is also found that using literary works in the teaching learning process can improve student’s ability both in micro-linguistics and macro-linguistics.